Biosensors Based on Advanced Sulfur-Containing Nanomaterials - Chunmei Li; Yihan Wang; Hui Jiang; Xuemei Wang (Sensors, 2020)
In recent years, sulfur-containing nanomaterials and their derivatives/composites have attracted much attention because of their important role in the field of biosensor, biolabeling, drug delivery and diagnostic imaging technology, which inspires us to compile this review. To focus on the relationships between advanced biomaterials and biosensors, this review describes the applications of various types of sulfur-containing nanomaterials in biosensors. We bring two types of sulfur-containing nanomaterials including metallic sulfide nanomaterials and sulfur-containing quantum dots, to discuss and summarize the possibility and application as biosensors based on the sulfur-containing nanomaterials. Finally, future perspective and challenges of biosensors based on sulfur-containing nanomaterials are briefly rendered.